An Integrated Approach Towards the Optimisation of Ventilation, Air Cooling and Pumping Requirements for Hot Mines (The Australasian Institute of Mining and Metallurgy, 2005)
This paper contends that optimisation of energy resources through active control and predictive simulation modelling is possible, and that such monitoring leads to large savings in the electricity costs of hot mines (where refrigeration has to be employed). In addition, active monitoring and control can positively affect the establishment of a safe, healthy and productive working environment. In the entire optimisation process certain guidelines were set to ensure that the requirements of the Mine Health and Safety Act were met (South Africa). Varying the quantity of air supplied underground by means of variable speed drive (VSD) fans is one of the crucial factors in the interactive approach towards the optimisation of ventilation, as is refrigeration and the pumping requirements associated with refrigeration. This article highlights the interaction between the amount of air supplied and the effect it has on refrigeration requirements underground. This article also considers the effect that this would have on contaminant control. Various tools are available for ventilation and cooling design for mining. A lot of these tools are based on the assumption of steady state conditions and do not take into account instantaneous changes in conditions, day-to-day, or hour-to-hour (such as for temperature and contaminants). They also do not take into account the optimisation of energy resources related to the creation of the acceptable underground conditions. With these tools worst-case and best-case scenarios are identified, and strategic decisions are made accordingly. Currently, the amount of the fresh air, the velocity of the air, and its general temperature in the mine are only changed when one production phase changes into another (or when unacceptable conditions occur as a result of poor design or neglect). This means that during a specific production phase (which can last for several months), there can be an oversupply, or undersupply, of energy resources, which will obviously affect the concentration levels of the various contaminants (through under or oversupply of air).